Midwifery Care in Multiparas with Diabetes Mellitus - Siti Choirul Dwi Astuti (JOURNAL OF NONCOMMUNICABLE DISEASES, 2021)
Comprehensive midwifery care is carried out to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). The goal is to provide comprehensive care so that pregnancy, childbirth, newborn and postpartum usually run. The research method used is a case study with a qualitative approach. Case studies used midwifery care in SOAP format ranging from data assessment, data analysis, and management. The results of the care provided starting from pregnancy, namely 14 standards during pregnancy, can be carried out, so that discomfort in the third trimester of pregnancy runs smoothly and maternal complaints can be resolved. All delivery care for multiparous mothers with diabetes mellitus was no different from standard delivery care during delivery. Newborns have average weight and are given the care to prevent hypoglycemia by initiating early breastfeeding in the first 1 hour after birth and rooming in the baby with the mother. HB-0 and vitamin K administration were continued, and the baby was healthy. The standard during the puerperium can all be done and given the care to reduce perineal pain and accelerate the healing of perineal wounds. The conclusion is that all means of midwifery care from pregnancy to the completion of the puerperium can be performed on multiparous mothers with diabetes mellitus, and there are no complications for the mother or baby